Linear actuator for the control of magnetic digital microfluidic systems - You, Junqiang (Nanyang Technological University, 2020)
This project aims to design and prototype with the consideration of the movement of droplets under magnet force. Droplets mixed with magnetic powder on Teflon coated glass which is held by a frame. Meanwhile, magnet held by an extension bar which is tightened on 3 axes device or actuator. As the magnet moves droplets move, here we use the Programmable Automation Controller -PAC to control the movement of magnetic force to control the movement of the droplets.